2006
DOI: 10.1074/jbc.m603963200
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Calcium- and Integrin-binding Protein 1 and the αIIb Integrin Cytoplasmic Domain Involves a Novel C-terminal Displacement Mechanism

Abstract: Calcium-and integrin-binding protein 1 (CIB1) regulates platelet aggregation in hemostasis through a specific interaction with the ␣IIb cytoplasmic domain of platelet integrin ␣IIb␤ 3 . In this work we report the structural characteristics of CIB1 in solution and the mechanistic details of its interaction with a synthetic peptide derived from the ␣IIb cytoplasmic domain. NMR spectroscopy experiments using perdeuterated CIB1 together with heteronuclear nuclear Overhauser effect experiments have revealed a well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
78
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(85 citation statements)
references
References 59 publications
5
78
0
2
Order By: Relevance
“…Chemical shift differences between the holo and apo forms of full-length OsCaM61 as well as between the full-length and truncated forms of holo-and apo-OsCaM61 were analyzed using Equation 2 (32). Chemical shifts obtained for deuterated samples through transverse relaxation optimized spectroscopy-based experiments were corrected for isotope shifts before further analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical shift differences between the holo and apo forms of full-length OsCaM61 as well as between the full-length and truncated forms of holo-and apo-OsCaM61 were analyzed using Equation 2 (32). Chemical shifts obtained for deuterated samples through transverse relaxation optimized spectroscopy-based experiments were corrected for isotope shifts before further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Papers were washed with 3 ϫ 500 ml of 0.5% (v/v) H 3 PO 4 (5 min each) and once with 500 ml of acetone (5 min) and left to dry. Subsequently, 32 P was quantified by Cerenkov counting (41). Calmodulin kinase II (CaMKII) was also purified from chicken gizzards (42,43).…”
Section: Methodsmentioning
confidence: 99%
“…These two crystal structures have a similar arrangement of the secondary structural elements, but large differences exist in their relative orientations of the N-and C-domains as well as the secondary structure of their N-and C-terminal extensions. Our initial residual dipolar coupling (RDC) 3 NMR study (12) suggested that the monomeric crystal structure of CIB1 (1XO5) more closely resembles the overall conformation of the protein in solution, except for its N-terminal extension.…”
mentioning
confidence: 99%
“…In addition, CIB1 contains a myristoylated N-terminal extension in vivo (16), and a short C-terminal extension that was postulated to be involved in a displacement mechanism to increase its target-binding specificity (12). So far, two x-ray crystal structures of Ca 2ϩ -CIB1 have been deposited in the Protein Data Bank, in which 1XO5 (15) is a monomer and 1Y1A (14) is a head-to-tail homodimer.…”
mentioning
confidence: 99%
See 1 more Smart Citation